Combining Electrosynthesis with Thermolysis: A Safe/Scalable Route to Multinary Oxide Semiconductor Films. Issue 7 (22nd March 2021) - Vali, Abbas; Jee, Hyung‐Woo; Myung, Noseung; Rajeshwar, Krishnan
Abstract: Adding a thermolysis step to electrosynthesis (as in "electrothermosynthesis") considerably enhances the scope of electrochemical film deposition and affords multinary compositions previously inaccessible by this otherwise versatile and mild synthetic approach. Copper pyrovanadate (β−Cu2 V2 O7 ), a member of the Cu−V−O family of ternary oxide semiconductors that are of considerable interest to the solar fuel community, is shown herein to be an exemplar of this approach. Finally, the generality of the hybrid approach is discussed for a variety of ternary metal oxides. Abstract : Electrothermosynthesis : Adding a thermolysis step to electrosynthesis considerably enhances the scope of electrochemical film deposition and affords multinary compositions previously inaccessible by this otherwise versatile and mild synthetic approach.